Creating and Implementing a Resident Emotional Wellness Initiative in an Acute Care Setting: The Role of the Palliative Care Social Worker. Issue 3 (2nd July 2020) - Weiner, Sheila B.
Abstract: Caring for dying patients is often a new experience for ICU residents. End-of-life and palliative training in medical schools is lacking. Many residents experience troublesome emotions during residency. Literature establishes that residents show lower well-being scores than similar populations. To make emotional wellness a priority for residents, monthly mandatory Palliative Care Rounds (PCR) were established in the ICU. The role of the Palliative Care Social Worker (PCSW) is central in planning and implementing PCR. Social workers have unique skills well-suited to this type of activity in an acute care setting. Residents present cases and the PCSW facilitates discussion to explore complex emotions helping residents process their feelings. Forty-five residents responded to a seven-item questionnaire, out of 70 potential resident respondents (64% response rate). Only 60% said they learned about end-of-life and its emotional aspects in medical school. Ninety-eight percent reported the PCR helped them be more aware of their feelings, and would recommend it to colleagues. Ninety-five percent said PCR are important for interns and residents to help them grow professionally and become better clinicians. Through the process of dissecting their emotions, PCR allows for personal and professional growth that improves residents' ability to become empathic providers.